Quantum chemical approach to atomic manipulation of chlorobenzene on the Si(111)-7×7 surface: Resonance localization, vibrational activation, and surface dynamics - Richard Palmer (Physical Review Materials, 2017)
We present a cluster model to describe the localization of hot charge carriers on the Si(111)-7×7 surface, which leads to (nonlocal) desorption of chlorobenzene molecules in scanning tunneling microscope (STM) manipulation experiments. The localized charge carriers are modeled by a small cluster. By means of quantum chemical calculations, this cluster model explains many experimental findings from STM manipulation. We show that the negative charge is mainly localized in the surface, while the positive one also resides on the molecule. Both resonances boost desorption: In the negative resonance the adatom is elevated; in the positive one the chemisorption bond between the silicon surface adatom and chlorobenzene is broken. We find normal modes promoting desorption matching experimental low-temperature activation energies for electron- and hole-induced desorption.